Early life interactions with aquatic insects elicit physiological and behavioral stress responses in lake sturgeon (Acipenser fulvescens) - Wassink, Lydia; Riedy, Joseph J.; Huerta, Belinda; Johnson, Garrett; Larson, Douglas L.; Li, Weiming; Scribner, Kim T. (Environmental Biology of Fishes, 2021)
Predator encounters during early life can elicit behavioral and physiological responses that have fitness consequences during subsequent prey life stages. In threatened lake sturgeon (Acipenser fulvescens) and other lithophilic-spawning fishes, newly hatched larvae (free embryos) are exposed to abundant predators including aquatic insect larvae that co-occupy stream substrates. We investigated stress effects on lake sturgeon larvae after encounters with common aquatic insect predators by quantifying mortality, body size, cortisol levels, and swimming behavior. Free embryos were exposed to either Perlidae (stonefly obligate predators) or Isonychiidae (mayfly filterers and facultative predators) or to no predators (controls). Free embryos that encountered perlids experienced high mortality, elevated cortisol levels, and exhibited cortisol reactivity when subsequently exposed to an acute stressor. Free embryos that encountered isonychiids exhibited elevated mortality, and elevated cortisol and cortisol reactivity relative to controls. Findings indicate that lake sturgeon free embryos are stressed by exposure to members of benthic stream communities during early life stages (predation of nearby conspecifics), and that metrics of stress exhibited threat sensitivity. Data are consistent with predictions that individuals modulate antipredator behavior in response to the intensity of perceived predation threat in the environment. We determined that behavioral outcomes associated with encounters with aquatic insects altered future behavioral trajectories, potentially as an adaptive response that can affect predation rates in subsequent life stages. Results contribute to a broader understanding of how interspecies interactions among co-occurring predator and prey communities may impact individual fitness and fish population recruitment.
Keywords: Aquatic invertebrates; Behavioral plasticity; Early life mortality; Lake sturgeon; Threat sensitivity; dept.che; peer-reviewed